2003
DOI: 10.1021/ja0360900
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of RNA Analogues Having Amides as Interuridine Linkages at Selected Positions

Abstract: Oligoribonucleotide analogues having amide internucleoside linkages (AM1: 3'-CH(2)CONH-5' and AM2: 3'-CH(2)NHCO-5') at selected positions have been synthesized and the thermal stability of duplexes formed by these analogues with complementary RNA fragments has been evaluated by UV melting experiments. Two series of oligomers with either 2'-OH or 2'-OMe vicinal to the amide linkages were studied. Monomeric synthons (3' and 5'-C amines and carboxylic acids) were synthesized as follows: For synthesis of the AM1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 75 publications
(100 reference statements)
7
96
1
Order By: Relevance
“…Backbone-modified RNA may find broad application in the fundamental biology and biomedicine of noncoding RNAs, providing that the modifications mimic the structure of the phosphodiester linkage and do not alter the conformation of RNA. In particular, the potential of RNA interference to become a new therapeutic strategy has revitalized interest in chemical modifications that may optimize the pharmacological properties of short interfering RNAs (siRNAs).[1] We are interested in hydrophobic nonionic mimics of the phosphate backbone, such as formacetals [2] and amides, [3] that may confer high nuclease resistance to siRNAs along with reduced charge and increased hydrophobicity. Earlier studies showed that 3'-CH 2 -CO-NH-5' internucleoside amide linkages (abbreviated here as AM1) were well-tolerated in the DNA strand of an A-type DNA-RNA heteroduplex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Backbone-modified RNA may find broad application in the fundamental biology and biomedicine of noncoding RNAs, providing that the modifications mimic the structure of the phosphodiester linkage and do not alter the conformation of RNA. In particular, the potential of RNA interference to become a new therapeutic strategy has revitalized interest in chemical modifications that may optimize the pharmacological properties of short interfering RNAs (siRNAs).[1] We are interested in hydrophobic nonionic mimics of the phosphate backbone, such as formacetals [2] and amides, [3] that may confer high nuclease resistance to siRNAs along with reduced charge and increased hydrophobicity. Earlier studies showed that 3'-CH 2 -CO-NH-5' internucleoside amide linkages (abbreviated here as AM1) were well-tolerated in the DNA strand of an A-type DNA-RNA heteroduplex.…”
mentioning
confidence: 99%
“…The tert-butyldimethylsilyl (TBS) groups in the known 3'-allyluridine 1 [3] were replaced with 5'-O-methoxytrityl (MMT) and 2'-O-acetyl protecting groups suitable for solid-phase RNA synthesis. Two-step oxidative degradation of the alkene gave the carboxylic acid part 6 of the r(U AM1 A) dimer.…”
mentioning
confidence: 99%
“…Olefin 11 was dissolved in dioxane-H 2 O, and catalytic amounts of OsO 4 were added with stoichiometric NMO acting as the reoxidizing agent. 14 The crude reaction product was then treated with NaIO 4 to afford aldehyde 12 in 74% yield. Subsequent oxidation with sodium chlorite in a buffered t-BuOH-H 2 O mixture in the presence of a halogen scavenger generated the corresponding carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Among the few exceptions are amides (3′-CH 2 -CONH-5′ and 3′-CH 2 NHCO-5′), [24][25][26] 27,28 formacetal (3′-OCH 2 O-5′), [29][30][31][32] and thioformacetal (3′-SCH 2 O-5′) 31,32 backbones. Recently, we showed that the two isomeric amide linkages (Figure 1, 1 and 2) were excellent mimics of the phosphodiester backbone in RNA duplexes.…”
Section: Introductionmentioning
confidence: 99%